Potensi Bioakumulator dan Hiperakumulator Lima Spesies Tanaman Sansevieria Berdaun Tebal Terhadap Logam Pb, Cd, Cu dan Zn - Tengku Nurhidayah; Muhammad Ali (Jurnal Zona, 2026)
This study critically assesses regional development policies on Sumbawa Island, particularly the PIJAR program (Cattle, Corn, and Seaweed) and the corn nomenclature, through the perspectives of environmental ethics and critical theory. Employing a mixed-method approach, the research integrates a spatial analysis of land cover changes in the Padolo River Basin during 2017-2024 with a policy text examination based on Jürgen Habermas's theory of the "Colonization of the Lifeworld." The findings reveal that these policies reflect structural anthropocentrism, prioritizing economic production targets over ecological integrity in a top-down fashion. The consequence is a destructive transformation of the regional landscape, where the depletion of upstream forests triggers Policy-Induced Disaster phenomena, including increased frequency of floods and extreme droughts. The study concludes that the ecological crisis on Sumbawa Island is the result of a failed development vision that neglects the carrying capacity of nature and the government's inability to provide alternative employment opportunities for the community